Analisis Kesesuaian Material Kayu untuk Konstruksi Eksterior pada Lingkungan Tropis : Suitability Analysis of Wood Materials for Exterior Construction in Tropical Environments - Fitria Cita Dirna; Isna Yuniar Wardhani; Resta Rene Mondina; Adika Archie Rosandy; Dimas Syawaldi; Ali Fajrul (JURNAL HUTAN TROPIKA, 2026)
This study aims to analyze the suitability of wood materials for exterior construction in tropical environments by considering structural functions, material characteristics, and the level of environmental exposure. The method employed was a qualitative descriptive approach through visual observation of several wood-based building objects, including residential houses, semi-open cafes, gazebos, and monuments. Data were collected through documentation and identification of construction elements, then classified based on wood species, element function, and suitability of use. The results indicate that wood with high strength and durability classes, such as ulin (E. zwageri) and bengkirai (Shorea laevis), is predominantly used in primary structural elements directly exposed to outdoor conditions, including columns, beams, and decking floors. Meanwhile, medium-strength wood such as meranti (Shorea spp.) and kamper (Dryobalanops aromatica) is more commonly applied in non-structural or semi-exterior elements with lower exposure levels. In addition, alternative materials such as bamboo and lightweight wood are utilized in secondary elements due to their efficiency and ease of construction. This study confirms that the suitability of wood materials in exterior construction is determined by the interaction between material properties, structural function, and environmental exposure level. The findings provide a conceptual basis for performance-based wood material selection to support adaptive and sustainable construction practices in tropical regions.